A bioinorganic approach to the study of the interactions of nitrogen oxides with manganese porphyrins and manganese- and cobalt-reconstituted myoglobin. - Zahran, Zaki Nabeih Ahmed. (My University, 2007)
This dissertation deals with the interaction of the biologically important nitrogen oxides (nitric oxide and nitrite) with manganese and ruthenium centers in small inorganic porphyrin and nonporphyrin complexes as well as with manganese and cobalt centers in manganese and cobalt substituted myoglobin.

Also we report the room and the low temperature (-78° C) cyclic voltammetric behavior of three six coordinate (por)Mn(NO)(1-MeIm) (por = tetraphenylporphyrin dianion (TPP), tetratolylporphyrin dianion (TTP) or tetra-p-methoxyphenylporphyrin dianion (T(p-OCH3)PP)) complexes at a Pt disc electrode in two nonaqueous solvents (CH2Cl2 and THF). In CH2Cl2 at room temperature, the compounds undergo four oxidations and two reductions within the solvent limit; in THF, the compounds undergo one oxidation and three reductions. In both solvents, the first oxidation represents a chemically irreversible one-electron process involving the rapid loss of nitric oxide. The oxidation occurs at the MnNO site as judged from bulk electrolysis, UV-vis spectroscopy at room temperature, and IR-spectroelectrochemistry at room temperature and at -78° C. The second oxidation, accessible in CH2Cl2, is also chemically irreversible and occurs at the porphyrin ring; the third and the fourth oxidations are, on the other hand, chemically reversible but also occur at the porphyrin ring. The first reduction is chemically irreversible in CH2Cl2, occurs at the porphyrin ring, and is followed by loss of NO. In THF, the first reduction is chemically reversible and is followed by reversible loss of NO.

Chapter 1 introduces the fundamental background of the biological importance of nitric oxide, nitrite, manganese porphyrins and manganese-reconstituted myoglobin.

Chapter 4 describes the 1.6--2.0 A resolution crystal structures of the as-isolated Mn-substituted horse heart myoglobin (hh MnIIIMb), the reduced form hh MnIIMb, and complexes of hh MnMb with methanol, azide, nitric oxide, and nitrite. The MnIIIMb compound contains distal pocket water in two positions, one coordinated and the other not coordinated. The reduced form, MnIIMb, lacks a distal pocket water molecule, in contrast to that observed previously for the iron-containing deoxy Mb. Interestingly, the structure of the NO adduct suggests a loosely bound NO in the distal pocket; the Mn--N--O moiety is surprisingly bent, and represents the first such distinctly bent metal-NO unit for a natural or synthetic manganese porphyrin complex. Both crystal structures of hh Mn IIIMb(ONO) and hh CoIIIMb(ONO) determined in this work also reveal this unusual nitrito coordination mode. In addition, this surprising result for the cobalt case, when compared with nitrite ligand orientations in related model compounds, demonstrates the importance of the Mb distal pocket in orienting the nitrite towards this O-binding mode.

Chapter 2 describes the preparation of the oxo-bridged dimer [Ru(bpb)(NO] 2(mu-O) in 60% isolated yield from the reaction of the known Ru(bpb)(NO)Cl with silver nitrite. The compound exhibits a upsilonNO of 1758 cm -1 (KBr pellet). The crystal structure reveals a linear ON-Ru-O-Ru-NO fragment with the oxo atom serving as an inversion center in the molecule. The redox behavior in DMF is characterized by a reversible reduction followed by a second but irreversible reduction in this solvent.

In summary, this dissertation shows that nitric oxide binds to the manganese center in a linear axial fashion in manganese porphyrin model compounds and in a bent tilted fashion in manganese-substituted myoglobin. Nitrite displays the O-binding coordination mode to both manganese model compounds and manganese-substituted myoglobin. Although nitrite exhibits the N-binding coordination mode in all known cobalt model compounds, it shows O-binding mode to cobalt-substituted myoglobin. The O-binding mode that nitrite exhibits to manganese- and cobalt-substituted myoglobin as well as that reported for ferric-myoglobin further demonstrates the crucial role of the distal amino acids in the heme pocket in changing the coordination preferences of ligands to metal center in myoglobin.

Chapter 3 describes the syntheses of a new set of six-coordinate manganese nitrosyl porphyrins of the general form (por)Mn(NO)(L) (por = TTP, TPP, T( p-OCH3)PP; L = piperidine, methanol, 1-methylimidazole) in moderate to high yields. The (por)Mn(NO)(pip) complexes were prepared from the reductive nitrosylation of the (por)MnCl compounds with NO in the presence of piperidine. The IR spectra of the (por)Mn(NO)(pip) compounds as KBr pellets show new strong bands at 1746 cm-1 (for TTP) and 1748 cm -1 (for (T(p-OCH3)PP) due to the NO ligands. Attempted crystallization of one of these compounds (por = TTP) from dichloromethane/methanol resulted in the generation of the methanol complex (TTP)Mn(NO)(CH3OH). Reaction of the (por)Mn(NO)(pip) compounds with excess 1-methylimidazole gave the (por)Mn(NO)(1-MeIm) derivatives in good yields. The IR spectra of these compounds show upsilonNO bands that are ∼ 12 cm-1 lower than those of the (por)Mn(NO)(pip) precursors, indicative of greater Mn→ NO pi-backdonation in the 1-MeIm derivatives. X-ray crystal structures of four of these compounds, namely (TTP)Mn(NO)(CH3OH), (TTP)Mn(NO)(1-MeIm), (TPP)Mn(NO)(1-MeIm), and (T(p-OCH3)PP)Mn(NO)(1-MeIm) were obtained, and reveal that the NO ligands in these complexes are linear.
Keywords: Nitric oxide.; Porphyrins.; Chemistry, Biochemistry.; Chemistry, Inorganic.; Myoglobin.